Evaluating the Holistic Review Process: Applicant Feedback. - Thompson, Terri; Millikan, Sarah (Journal of Nursing Education, 2025)
Background: Holistic reviews play a crucial role in enhancing the diversity of health care workers, ensuring they can meet the needs of a varied population. Although extensive research highlights the importance of holistic reviews, there is a noticeable gap in understanding how applicants perceive this process. Method: A pre- and postinterview survey was given to 279 applicants, over three separate holistic interview events. The participants included individuals applying for both the Bachelor of Science in Nursing and Entry Level Master of Science in Nursing (EL-MSN) programs. Results: The results showed that 88% of applicants perceived they could effectively demonstrate their valuable qualities and attributes during the holistic review process. Conclusion: Holistic admissions, when implemented using best practices, can incorporate diverse activities in interviews. These diverse activities highlight each applicant's unique qualities and attributes, allowing admission committees to get a well-rounded view of the applicants.